2013
DOI: 10.1097/mph.0b013e318288634d
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Site of Metastases and Outcome in Children With Stage IV Wilms Tumor

Abstract: Summary:The aim of this study was to analyze in detail the site of metastasis of stage 4 Wilms tumor (WT) and its correlation with outcome. The databases from 3 major European pediatric cancer institutions were screened for children with WT between 1994 and 2011. Of 208 children identified, 31 (14.9%) had metastases at diagnosis. The lung was affected in 29 children (93.5%) and the liver in 6 children (19.4%). Twenty-seven children (87.1%) had metastases isolated to 1 organ, with the lung being the most common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…[12] Smets et al reported that lung biopsies obtained after treatment with preoperative chemotherapy were positive for tumor (or necrotic tumor) in 85% (17/20) of patients. [21] Some in both of these series were also reported by Berger et al [22] The finding that outcome is better for patients with CT-only lung nodules than for those with nodules detectable by plain chest radiograph [19,21,23] supports several interpretations, including that some patients with CT-only nodules have only benign nodules and the volume of disease is less among those with CT-only nodules compared to nodules identified on plain chest radiograph.…”
supporting
confidence: 72%
“…[12] Smets et al reported that lung biopsies obtained after treatment with preoperative chemotherapy were positive for tumor (or necrotic tumor) in 85% (17/20) of patients. [21] Some in both of these series were also reported by Berger et al [22] The finding that outcome is better for patients with CT-only lung nodules than for those with nodules detectable by plain chest radiograph [19,21,23] supports several interpretations, including that some patients with CT-only nodules have only benign nodules and the volume of disease is less among those with CT-only nodules compared to nodules identified on plain chest radiograph.…”
supporting
confidence: 72%
“…Reports from other developing African countries indicate a higher incidence of stage IV WT among their cohorts, with a reported incidence of 30.9%, 40%, and 42% in Nigeria, Kenya, and South Africa, respectively [8,9]. While in developed countries, the incidence is relatively lower, with a reported incidence of 12%, 14.9%, and 17% in Children Oncology Group (COG), German study, and International Society of Pediatric Oncology (SIOP), respectively [10,11]. This high incidence of advanced stages of WT noticed in developing countries could be attributed to several factors such as lack of awareness among caregivers and healthcare professionals regarding early presentations of WT, limited resources and poor access to health care that lead to late presentations, and advanced disease stage at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Even in advanced tumor stages, complete excision of the urinary tract tumor and optimal treatment of disseminated malignancy are pivotal to overall patient management and outcome. Increased global reporting of ureteric involvement by nephroblastoma is necessary to determine the exact significance of the different involvement patterns, especially when metastatic disease is well controlled with current and emerging therapeutic modalities [28]. More detailed prospective studies, including phenotypic, immunophenotypic and genotypic appraisal of the ureteric component of nephroblastomas that have not been exposed to neoadjuvant chemotherapy may be helpful in determining potential associations between ureteric involvement and the biological profile of the primary renal and contiguous ureteric tumoral components.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the aim of current nephroblastoma management schedules, within and beyond the confines of the kidney and ureter, is to control disease and improve patient quality of life. Chemotherapy, radiation and metastatectomy may be employed to ensure such management objectives [28], but the latter is relatively new practice in our center; metastatic disease in the study patients was managed by chemoradiation exclusively.…”
Section: Discussionmentioning
confidence: 99%